2004
DOI: 10.1590/s0103-64402004000100007
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of the effectiveness of different concentrations of sodium hypochlorite associated with rotary instrumentation for root canal cleaning

Abstract: This study evaluated the cleaning capacity of Profile.04 instruments with different concentrations of NaOCl solutions on flattened root canals. Twenty central mandibular incisors were divided into 4 groups: Group I: 0.5% NaOCl; Group II: 1% NaOCl; Group III: 5% NaOCl; Group IV: distilled and deionized water. After chemomechanical preparation, the teeth were submitted to histological preparation and morphometric analysis. Morphometric analysis showed that the 5% NaOCl was significantly more efficient in cleanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 12 publications
1
21
0
5
Order By: Relevance
“…This reaction can be accentuated by continuous flux and larger amount of solution, which would provide the effective removal of superficial debris and prolongation of the chemical activity of the solution (7,9). According to Baratto-Filho et al (6), rotary instrumentation combined with NaOCl irrigation at different concentrations between each instrument evidenced greater debris removal for the 5% NaOCl solution when compared to the 0.5% solution, whereas in the present study, the increased concentration in the final irrigation did not contribute to canal cleaning. On the other hand, other authors observed that in the final irrigation, the NaOCl energized with ultrasound contributed to debris removal, in comparison to distilled water energized by ultrasound as well (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reaction can be accentuated by continuous flux and larger amount of solution, which would provide the effective removal of superficial debris and prolongation of the chemical activity of the solution (7,9). According to Baratto-Filho et al (6), rotary instrumentation combined with NaOCl irrigation at different concentrations between each instrument evidenced greater debris removal for the 5% NaOCl solution when compared to the 0.5% solution, whereas in the present study, the increased concentration in the final irrigation did not contribute to canal cleaning. On the other hand, other authors observed that in the final irrigation, the NaOCl energized with ultrasound contributed to debris removal, in comparison to distilled water energized by ultrasound as well (13).…”
Section: Discussionmentioning
confidence: 99%
“…However, nickel-titanium instruments are not effective for cleaning flattened root canals, or those in which the canal shape does not allow instrumentation (4,5). In these situations, irrigant solutions may assume fundamental importance in biomechanical preparation (6). Among these solutions advised for biomechanical preparation, sodium hypochlorite, at different concentrations, is the most used due to its properties of clarification, organic tissue dissolution, saponification, transformation of amines into chloramines, deodorization and antimicrobial action (7,8).…”
Section: Effectiveness Of Different Final Irrigation Protocols In Remmentioning
confidence: 99%
“…Several studies (8,18) evaluated the cleaning ability of RaCe rotary system. Even with the continuous and expansive development of instruments and preparation techniques, scientific literature has reported that there is not a single technique nor instrument system that totally cleans the root canal (5).…”
Section: Discussionmentioning
confidence: 99%
“…Esta análise consistiu em dividir a imagem em 100 quadrados, cada um com a mesma área. Similar metodologia foi empregada por MARCHESAN et al, 2003;BARATTO-FILHO et al, 2004;FORNARI et al, 2010;GONÇALVES et al, 2010. A análise morfométrica foi realizada em vista que a Ferramenta Z-Stack do software Leica LAS-AF, somente mede a espessura do biofilme desde sua parte mais alta até a superfície dentinária, sem ter em consideração a biomassa total na superfície dos blocos de dentina. (ANEXO I).…”
Section: Da Metodologiaunclassified